Pengaruh Pemberian Myofascial Release Dan McKenzie Exercise Terhadap Penurunan NyeriPasien Low Back Pain Mekanik Di Rsud Cilacap - Husada, Aditya Angga; , Dwi Rosella K, S.Fis, M.Fis; , Isnaeni Herawati, SST. FT, M.Sc (2016)
The Background: LBP is a pain that occurs in the lower back area, while the mean LBP mechanics is the type of LBP to cause trauma and mechanical factors. Physiotherapy has several user modalities that can be used to treat LBP, including Myofascial Release and Mc kenzie exercise where both modalities are intended to relieve pain, increase range of motion. Objective: To determine the effect of the differences between myofascial release with the McKenzie exercise on pain reduction of mechanical LBP. Methods: This was an experimental, two-group pretest and posttest design. The samples were taken using purposive sampling techniques and using inclusion and exclusion criteria. The samples were divided into two groups, one group was given myofascial release, while the second group was given the McKenzie exercise. The study was conducted 3x / week for 6x therapy. Results: The effect test of the treatment group myofascial release p value = 0.018 (p <0.05) while the effect test of the treatment group exercise Mc Kenzie was p value = 0.018 (p <0.05). The different test after treatment between groups 1 and 2 was p value = 0.224 (p> 0.05) Conclusion: Myofascial Release and Mc Kenzie exercise are equally influential in reducing pain in mechanical LBP and both are good, there is not the difference in reducing pain in mechanical LBP.